2004
DOI: 10.1123/tsp.18.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Is What You See Really What You Get? Athletes’ Perceptions of Imagery’s Functions

Abstract: Imagery in sport has been studied extensively (for a review see Martin, Moritz, & Hall, 1999). Researchers have described the what, why, where, when, and how athletes use imagery (e.g., Martin et al., 1999; Munroe, Giacobbi, Hall, & Weinberg, 2000). Most of the current research in this area has supported Paivio's (1985) conceptualization of imagery into cognitive and motivational functions that operate on specific and general levels. These functions are Cognitive Specific (CS: imaging skills), Cognitive Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 9 publications
11
36
0
Order By: Relevance
“…Evans et al (2006) recommend that the AIIQ-2 should be improved through including participants' perceptions of what the purpose of the imagery is so that it can be correctly categorized to the right subtype of imagery. This recommendation is consistent with that of Short, Monsma, and Short (2004) who state that the intended goal of the imagery should be recorded. Regardless of these factors, the AIIQ-2 still stands as the best quantitative questionnaire to assess athletes' frequency of imagery use prior to and during injury rehabilitation.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Evans et al (2006) recommend that the AIIQ-2 should be improved through including participants' perceptions of what the purpose of the imagery is so that it can be correctly categorized to the right subtype of imagery. This recommendation is consistent with that of Short, Monsma, and Short (2004) who state that the intended goal of the imagery should be recorded. Regardless of these factors, the AIIQ-2 still stands as the best quantitative questionnaire to assess athletes' frequency of imagery use prior to and during injury rehabilitation.…”
supporting
confidence: 84%
“…It is also possible that the reading of the cue from the AIIQ-2 could have sparked the athletes in the control group to retrospectively link thoughts of healing they may have had at some point in their recovery and cause them to portray that they used that function of imagery more frequently than they actually did. The suggestion by Short et al (2004) for the AIIQ-2 to include athletes' perceptions of the purpose of their images could aid in combating this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that images can serve multiple functions for athletes (Nordin & Cumming, 2008;Short, Monsma & Short, 2004). Two judokas use a variety of sensory modalities visualizing the execution of techniques.…”
Section: Introductionmentioning
confidence: 99%
“…I also clarified that in time, the image could encourage an external focus before shot execution (i.e., a focus on the effect in the environment that is produced as the result of body movement), which should encourage optimal performance under pressure (Wulf & Jiang, 2007;PerkinsCeccato, Passmore, & Lee, 2003). I asked both Adam and Chris to persist with the imagery and offered them various scripts based on contemporary literature (e.g., Short, Monsma, & Short, 2004) that were designed to improve their imagery ability.…”
Section: Off-season (January-march)mentioning
confidence: 99%